Impact of Dynamic Soil–Structure Interaction on the Response of Liquid-Storage Tanks - Tsipianitis, Alexandros; Tsompanakis, Yiannis; Psarropoulos, Prodromos N. (Frontiers in Built Environment, 2020)
In general, soil-structure interaction phenomena affect considerably the dynamic response of liquid-storage tanks. As it is also observed in the case of ordinary structures, the ground motion transmitted to the superstructure can be amplified (or even de-amplified) due to the presence of the underlying soil layer(s), modifying in parallel the resonant period and the effective damping of structures. Typically, fixed-base liquid storage tanks are characterized by low fundamental periods. However, many such critical structures are located in coastal areas with soft soils, thus, the seismic performance of the superstructure may be notably different compared to stiff soil conditions. Therefore, ignoring soil-structure interaction may lead to unrealistic results. Accordingly, the influence of soil conditions in the dynamic response of liquid-storage tanks is investigated in the present study. More specifically, the dynamic soil-structure interaction of cylindrical steel tanks subjected to different ground motions is numerically examined. The main aim is to investigate the dynamic response and the distress of squat and slender liquid-storage tanks for different foundation conditions. The finite-element models include suitable contact formulations to accurately model the soil-structure interaction for each type of fixity conditions (i.e., anchored and unanchored).